Influence of alloy buffer and capping layers on InAs/GaAs quantum dot formation - Dasika, V. D.; Song, J. D.; Choi, W. J.; Cho, N. K.; Lee, J. I.; Goldman, R. S. (AMER INST PHYSICS, 2009)
We have investigated the influence of alloy buffer and capping layers on the shape, size, and density of self-assembled InAs/GaAs quantum dots. Cross-sectional scanning tunneling microscopy (XSTM) images reveal ellipse-shaped dots with highest (lowest) diameter, height, and density, for dots with (without) surrounding alloy layers. Furthermore, the wetting layer is thicker in the presence of the alloy layers. We propose a strain-based mechanism for dot formation and collapse in the absence and presence of alloy buffer and capping layers. This mechanism is likely to be applicable to a wide range of lattice-mismatched thin-film systems. (C) 2009 American Institute of Physics. [doi: 10.1063/1.3243688]
Keywords: MOLECULAR-BEAM EPITAXY; WETTING LAYERS; GAAS; INTERDIFFUSION; EVOLUTION; GROWTH; INGAAS